Valorizing Grape Pomace: A Review of Applications, Nutritional Benefits, and Potential in Functional Food Development - Vladimir S. Kurćubić; Nikola Stanišić; Slaviša B. Stajić; Marko Dmitrić; Saša Živković; Luka V. Kurćubić; Vladimir Živković; Vladimir Jakovljević; Pavle Z. Mašković; Jelena Mašković (Foods)
Grape pomace (GP), a byproduct of winemaking, has gained significant attention as a sustainable and functional ingredient with applications in the food and nutraceutical industries. This review examines the potential of GP in meat products and analogs, functional foods, and nutraceuticals, highlighting its composition, health benefits, and role in enhancing nutritional and functional properties. Rich in dietary fiber, polyphenols, essential fatty acids, and bioactive compounds, GP exhibits antioxidant, anti-inflammatory, and gut health-promoting effects, making it suitable for various food applications. Its incorporation into meat products, such as sausages and patties, improves texture, enhances shelf life, and increases nutritional value while reducing the environmental footprint. GP is also effective in functional foods such as baked goods, dairy and plant-based yoghurts, smoothies, and snack bars, where it can enrich fiber and polyphenol content, aid in satiety, and provide health benefits beyond basic nutrition. The challenge is how to maintain the sensory properties characteristic of conventional, unmodified products. In nutraceuticals, GP’s polyphenolic compounds and dietary fiber support antioxidant, anti-inflammatory, and metabolic health functions, with applications as antioxidant supplements, gut health boosters, weight management aids, and cardiovascular health supplements. Despite challenges such as taste modification and optimizing bioavailability, GP’s versatility and sustainability highlight its value in developing innovative, health-oriented products. This review emphasizes the promise of GP as a valuable ingredient in functional foods and nutraceutical formulations, contributing to health, sustainability, and resource efficiency.